2017
DOI: 10.1186/s13098-017-0289-y
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide attenuates atherosclerosis via inhibiting ER-induced macrophage derived microvesicles production in T2DM rats

Abstract: BackgroundWe investigated the effects of liraglutide on the formation and progression of atherosclerosis in type 2 diabetes mellitus (T2DM) rats.MethodsSprague–Dawley rats were divided into control group, diabetes group and liraglutide treated group. The T2DM rats model with atherosclerosis were induced by high fat diet followed small dosage streptozotocin injection. Body weight and blood glucose levels were monitored once a week for 3 months and then the rats were sacrificed.Peripheral blood and aorta tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…Previous reports have shown that beta-cell volume decreased by 63% in obese T2DM patients due to increasing threefold beta-cell apoptosis [16], which suggested that improvement of beta-cell dysfunction may be an important therapeutic strategy for the treatment of T2DM. GLP-1 is an incretin hormone secreted by intestinal epithelial L cells that promotes glucose-dependent insulin secretion, decreases glucagon secretion, stimulates beta-cell proliferation, suppresses apoptosis, and restores the function of islet beta-cells [1719]. It is widely recognized that T2DM in East Asians is characterized primarily by beta-cell dysfunction, which is evident immediately after ingestion of glucose or meal, and less adiposity compared to the disease in Caucasians [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that beta-cell volume decreased by 63% in obese T2DM patients due to increasing threefold beta-cell apoptosis [16], which suggested that improvement of beta-cell dysfunction may be an important therapeutic strategy for the treatment of T2DM. GLP-1 is an incretin hormone secreted by intestinal epithelial L cells that promotes glucose-dependent insulin secretion, decreases glucagon secretion, stimulates beta-cell proliferation, suppresses apoptosis, and restores the function of islet beta-cells [1719]. It is widely recognized that T2DM in East Asians is characterized primarily by beta-cell dysfunction, which is evident immediately after ingestion of glucose or meal, and less adiposity compared to the disease in Caucasians [20].…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic syndrome prevalence was significantly reduced (Rizzo et al, 2016). Dr. Li found that liraglutide attenuated the atherosclerotic lesion and plaque progression in aortic tissues induced by high fat diets followed by low-dose streptozotocin injection in type 2 DM rats (Li et al, 2017). Rizzo et al proposed that liraglutide exerted favorable cardiovascular effects through its direct antiatherosclerotic action, as well as its ability to prevent plaque formation and progression beyond glycemic control (Rizzo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As summarized in Table 1 , studies in rodents and rabbits have shown beneficial actions of GLP1As in atherosclerosis, vascular injury, and cardiac function. Liraglutide treatment in diabetic rats led to diminished atherosclerotic lesion formation and intima-media thickening through a decrease of macrophage secretion of ER-stress induced microvesicles [ 51 ]. Similarly, the expression of GLP1 by adenovirus-mediated delivery in diabetic rats reduced intima-media thickening, VSMC and monocyte migration, and inflammatory processes [ 52 ].…”
Section: Therapies Based On the Incretin Systemmentioning
confidence: 99%